POTRET EFEKTIFITAS GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN DISIPLIN SISWA - Ridwan, Ahmad; Fitriani, Fitriani; Satira, Ulfa (Al Jabiri: Jurnal Ilmiah Studi Islam, 2022)
This paper discusses the effectiveness of Islamic religious education teachers in fostering student discipline to enhance learning activities in the Islamic field. teachers are (a) the personality of the students so that they are self-aware by providing religious advice and providing an understanding of various kinds of Islamic education (b) making Islamic religious rules to shape the Islamic religion, learning students to govern good and prohibiting evil (c) providing training and habituation repeatedly, namely training, students to practice the material in the learning process (d) provides an imbalance and deterrent punishment that will shape student discipline. Students who behave and give punishment to naughty students and can commit violations.